Authenticity and employee wellbeing with reference to emotional work: a review. Issue 2 (12th March 2021) - Mehta, Poonam
Abstract : Purpose: In the service industry, there is an involvement of the human factor which comprises continuous interpersonal interactions. Sometimes, these interactions create incongruence between displayed and felt emotions which distract the employees from their authentic self and impair their well-being. This paper aims to made an attempt to review different studies to identify an association between authenticity at the workplace and employee well-being with reference to emotional work. Design/methodology/approach: The different studies have been reviewed mentioning the association between authenticity at the workplace and employee well-being with reference to emotional work published during the period of 1983–2020. The database which is used to identify and extract the research papers includes APA PycNET, Business Perspectives, Elsevier, Emerald Insight, Inderscience Publishers, SAGE, Taylor and Francis, etc. The keywords used for shortlisting the studies include employee well-being, emotional work, emotional dissonance, job satisfaction, surface acting, authenticity, burnout, authentic living, self-alienation. Findings: The study has determined that emotional work influences the authenticity of an employee which further impacts the well-being of employees. Research limitations/implications: The present review would aid the researchers in explaining the relevance of authenticity at the workplace for enhancing the employee well-being specifically in emotional work settings. Social implications: Promoting well-being at the workplace requires an action-oriented approach from the national level also. Hence, the present study may help in drawing inferences for framing well-being policies for employees at the national level. Originality/value: The paper is amongst the few reviews which have analysed the substantial role of authenticity in the context of emotional work to improve employee well-being.